56y=57

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

5⋅7=6y⋅5

Rewrite the equation as 6y⋅5=5⋅7.

6y⋅5=5⋅7

Simplify.

Multiply 5 by 6.

30y=5⋅7

Multiply 5 by 7.

30y=35

30y=35

Divide each term by 30 and simplify.

Divide each term in 30y=35 by 30.

30y30=3530

Cancel the common factor of 30.

Cancel the common factor.

30y30=3530

Divide y by 1.

y=3530

y=3530

Cancel the common factor of 35 and 30.

Factor 5 out of 35.

y=5(7)30

Cancel the common factors.

Factor 5 out of 30.

y=5⋅75⋅6

Cancel the common factor.

y=5⋅75⋅6

Rewrite the expression.

y=76

y=76

y=76

y=76

y=76

The result can be shown in multiple forms.

Exact Form:

y=76

Decimal Form:

y=1.16‾

Mixed Number Form:

y=116

Solve for y 5/(6y)=5/7